Pendampingan Perancangan dan Pemanfaatan Aplikasi Gamifikasi dalam Pembelajaran di SMP Al-Irsyad Kota Ternate - Nurdin Abdul Rahman; Saprudin Saprudin; Rahim Achmad; Fatma Hamid; Mardia Hi. Rahman; Nurlaela Muhammad; Sumarni Sahjat; Erni Arfa; Wa Mirna La Misran; Arvitarli Arman; Mawaddah S. Kippu (Arfah BHMS Foundation, 2026)
This article describes a community service (PKM) activity related to mentoring in designing and utilizing gamification applications in learning at the partner school. This PKM activity involved the PKM team, students, teachers, and educational staff at Al-Irsyad Junior High School in Ternate City. Data related to teacher competency achievement at the partner school was collected using performance observation sheets and product assessments. Data analysis was conducted using descriptive quantitative techniques. This PKM activity resulted in knowledge transfer and technology product transfer, as well as increased teacher competency at the partner school in designing and utilizing gamification applications in learning.